Health Technology Assessment of Advanced Therapy Medicinal Products: Comparison Among 3 European Countries - Gozzo, Lucia; Romano, Giovanni Luca; Romano, Francesca; Brancati, Serena; Longo, Laura; Vitale, Daniela Cristina; Drago, Filippo (Frontiers in Pharmacology, 2021)
Even for products centrally approved, each European country is responsible for the effective national market access. This step can result in inequalities in terms of access, due to different opinions about the therapeutic value assessed by Health Technology Assessment (HTA) bodies. Advanced therapy medicinal products (ATMPs) represent a major issue as regards to the HTA assessment in order to make them available at national level. These products are based on genes, tissues or cells, commonly developed as one-shot treatment for rare or ultra-rare diseases and mandatorily authorised by EMA with central procedure. This study aims to provide a comparative analysis of HTA recommendations issued by European countries (France, Germany and Italy) following EMA approval of ATMPs. We found a low rate of agreement on the therapeutic value (in particular the ‘added value’ compared to the standard of care) of ATMPs. Despite the differences in terms of clinical assessment, the access has been usually guaranteed, even with different timing and limitations. In view of the importance of ATMPs as innovative therapies for unmet needs, it is crucial to understand and act on the causes of disagreement among the HTA assessments. In addition, the adoption of the new EU Regulation on HTA would be useful to reduce disparities of medicines assessment among European countries.